2004
DOI: 10.1021/ol049700p
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Protonated Threonine, Its Stereoisomers, and Its Homologues in the Gas Phase:  Evidence for Internal Backside Displacement

Abstract: Protonated threonine and its allo diastereomer exhibit different proportions of collisionally activated dissociation (CAD) product ions. N-Methylation attenuates these differences. Water loss from protonated allo-threonine gives protonated trans-3-methylaziridinecarboxylic acid via an internal S(N)2 pathway, rather than protonated vinylglycine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…One pathway (Scheme 1) leads to formation of an aziridine ring on water loss. This pathway has been shown to be operative in loss of H 2 O from protonated serine and threonine [12][13][14]. A second pathway involves (Scheme 3) formation of an oxazoline upon elimination of H 2 O.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One pathway (Scheme 1) leads to formation of an aziridine ring on water loss. This pathway has been shown to be operative in loss of H 2 O from protonated serine and threonine [12][13][14]. A second pathway involves (Scheme 3) formation of an oxazoline upon elimination of H 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies concerning the mechanism of water loss from protonated serine and threonine and their derivatives. For protonated serine and threonine, it has been shown that attack of the amino group in the hydroxyl-protonated form leads to water loss and formation of a protonated three-membered aziridine ring [12][13][14]. By contrast, in N-acetyl derivatives interaction of the carboxyl group with the side-chain protonated hydroxyl group leads to formation of a protonated five-membered oxazoline ring upon loss of water [13].…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] Thr-containing peptides usually show many special characteristics upon CID and mechanisms into their fragmentation behavior have been reported. Loss of water upon CID is common for Thrcontaining peptides and has been proposed to form an aziridine ring [27][28][29] involving C α , C β , and the nitrogen of the amino group or of the peptide bond. It was also found that in the product ion spectra of doubly charged peptides, cleavages N-terminal to Ser and Thr show slightly enhanced tendency in comparison with cleavages C-terminal to these residues.…”
Section: Introductionmentioning
confidence: 99%
“…The water losses from the side chain of hydroxyl group containing amino acid residues have been extensively investigated by several groups [29][30][31][32][33][34][35][36]. In line with these works, a possible mechanism for the formation of m/z 279 fragment ion from protonated b 5 ion of SGGFL-NH 2 is shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 91%